Pemberdayaan Masyarakat Desa Puspahiang Kabupaten Tasikmalaya Melalui Penerapan Teknologi Biopori dalam Pemupukan: Community Empowerment at Puspahiang District Tasikmalaya Village by Application of Biopori Technology during Fertilization - Ulpah Jakiyah; Dona Setia Umbara; Selvy Isnaeni; Ovie Khopipah; Siti Karmilah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
The limited knowledge of farmers in cultivating mangosteen causes the quality of the trees to decrease—the decreasing number of production evidence this. So there is a need for efforts to increase mangosteen production with good cultivation or farming techniques. So this service activity is to conduct fertilization training with the bio-pore technique, which can reduce yellow sap contamination and provide calcium according to the tree's needs. This service's stages include counseling and socialization of bio-pore fertilization, land measurements, and satisfaction surveys. In addition, measurements of soil nutrients with acidity levels were carried out to help farmers deal with fruitless trees. As a result of the bio-pore installation activity, 80% of the farmers can understand and will apply the bio-pore technique to the farmers' mangosteen fields.